Ependyma‐expressed CCN1 restricts the size of the neural stem cell pool in the adult ventricular‐subventricular zone. (3rd February 2020) - Wu, Jun; Tian, Wen‐Jia; Liu, Yang; Wang, Huanhuan J; Zheng, Jiangli; Wang, Xin; Pan, Han; Li, Ji; Luo, Junyu; Yang, Xuerui; Lau, Lester F; Ghashghaei, H Troy; et al.
Abstract: Adult neural stem cells (NSCs) reside in specialized niches, which hold a balanced number of NSCs, their progeny, and other cells. How niche capacity is regulated to contain a specific number of NSCs remains unclear. Here, we show that ependyma‐derived matricellular protein CCN1 (cellular communication network factor 1) negatively regulates niche capacity and NSC number in the adult ventricular–subventricular zone (V‐SVZ). Adult ependyma‐specific deletion of Ccn1 transiently enhanced NSC proliferation and reduced neuronal differentiation in mice, increasing the numbers of NSCs and NSC units. Although proliferation of NSCs and neurogenesis seen in Ccn1 knockout mice eventually returned to normal, the expanded NSC pool was maintained in the V‐SVZ until old age. Inhibition of EGFR signaling prevented expansion of the NSC population observed in CCN1 deficient mice. Thus, ependyma‐derived CCN1 restricts NSC expansion in the adult brain to maintain the proper niche capacity of the V‐SVZ. Synopsis: The maintenance and activation of NSCs are regulated by niche components in the adult brain. Matricellular protein CCN1 is secreted from ependymal cells and negatively regulates the number of NSCs through restricting niche capacity in the adult V‐SVZ. Matricellular protein CCN1 is specifically expressed in the ependymal cells in the adult V‐SVZ. CCN1 restricts the capacity of the V‐SVZ NSC niche and the number of NSCs. CCN1 suppresses the expansion of NSC pool through inhibiting EGFR signaling. Abstract : Secretion of the matricellular protein CCN1 from ependymal cells regulates adult neural stem cell (NSCs) expansion but also the capacity of stem cell niches for holding a specific number of NSCs and their progeny.